"The dark place where talent leads": the merits and shortcomings of feminist criticism in the study of selected works by Christa Wolf - Weingartz, Gisela (University of the Free State, 2001)
During earlier research, it became evident Feminist Literary Criticism could offer useful insights when reading Christa Wolfs work. At the same time, such criticism revealed certain limitations which inhibit a full and accurate reading of Wolfs work. Given this situation, an exploration of the merits and shortcomings of Feminist Literary Criticism when applied to selected works of Christa Wolf became necessary. The research question has been articulated thus: What are the merits and shortcomings of Feminist Literary Criticism when applied to selected works of Christa Wolf? Because the Feminist Movement lacks dominant theory, the question arises whether Feminism can be seen as a literary theory/criticism that can serve as an appropriate means of investigating Christa Wolfs work. A corollary to the research question consequently emerged: does Feminism offer a literary theory or rather a philosophy/ideology based on a diversity of presumptions, gender included? In order to seek answers to these questions, the following dimensions are addressed: (a) A brief historical background and critical overview of Feminism; (b) An exploration of the multiplicity and diversity of the Feminist approaches and methodologies and the question of whether an integrated Feminist theory exists at present; (c) A further exploration of differences between the Anglo-American and French 'schools' of Feminist because such theories impact upon the study; German Feminist Criticism is also dealt with; (d) A consideration of debates concerning the terms female writing, feminist writing and feminine writing based on Feminist distinctions between female, feminist and feminine as well as the difference between gender and sex. (e) A consideration of Christa Wolf's creative vision of a Utopian Society and its relationship to the Feminist Movement's critical stances towards patriarchies throughout history. (f) A discussion of the discrepancies between female and feminist re-tellings of mythical materials as well as the manner in which Wolf deconstructs and reconstructs prehistoric myth in such a way that patriarchal misrepresentations are made evident. This dissertation consists of five chapters. The opening chapter offers a critical overview of the main premises of Feminist Criticism, drawn from major and/or contemporary sources. Part of this discussion falls on writings generated especially by German and American feminist critics who focus on the reception of Christa Wolfs work. The focal point of discussion is whether the Feminist Movement offers a literary-critical theory that can be applied meaningfully to the works of Christa Wolf. Chapter 1 is followed by three chapters (Chapters 2, 3, and 4), each devoted to discussion of an individual text by Wolf: Nachdenken Ober Christa T., Kassandra and Medea respectively. Methodologically, each chapter manifests a tripartite structure consisting of (a) a detailed discussion of Feminist Criticism of the specific text; (b) a hermeneutic examination of the text itself; and (c) an explication of the similarities and differences between (a) and (b) to show the merits and shortcomings of Feminist criticism of the text. The penultimate chapter, Chapter 5, examines some of Wolfs non-fictional work with a view to delineating her perspectives on the major gender themes and motifs in her fiction while the final chapter offers a discussion of the findings. The dissertation concludes with a list of references.
Dissertation (M.A. (German))--University of the Free State, 2001
Keywords: Quatations in German; Wolf, Christa -- Criticism and interpretation; German fiction -- 20th century -- History and criticism